Chateaubriand… Hugo…nothing… everything (a daydream) - Barbosa, Sidney; Prado, Márcio Roberto (Lettres Françaises, 2008)
This paper is built in the form of a poetic daydream to put side by side two features of the French writer Victor Hugo, that is, his political involvement in the society of his time and the aesthetic stances he assumed as a poet and writer. Trying to create a bridge between those two features, this essay allows that a figure of a quite mystic character be appreciated in the end, including his titanic prominence, capable of condensing in his personal epopee the historical moment he lived in as well as the exceptional literary contribution he has bequeathed.